PENGARUH SUSTAINABILITY REPORTING DISCLOSURE INDEX DAN FINANCIAL DISTRESS TERHADAP PENERIMAAN OPINI AUDIT GOING CONCERN PADA PERUSAHAAN ENERGY YANG TERDAFTAR DI BURSA EFEK INDONESIA - AIDA SAPITRI, SISKA; Saputra, Dian (UIR Press, 2025)
This research aims to determine the influence of Sustainability Reporting Disclosure Index and Financial Distress on the acceptance of Going Concern Audit Opinions in Energy Companies Listed on the Indonesia Stock Exchange in 2021-2022. The dependent variable of this research is Going Concern Audit Opinion, while the independent variables are Sustainability Reporting Disclosure Index and Financial Distress as well as the control variables Company Size, Leverage and Profitability. The population in this study was 95 Energy Sector companies registered on the IDX for the 2021-2022 period. This research sample consisted of 51 companies selected using purposive sampling techniques, with an observation period of 2 years, resulting in 102 company data. Data analysis uses multiple linear regression analysis using E-views 12. The results of the research show that partially the Sustainability Reporting Disclosure Index has no effect and is not significant on the Going Concern Audit Opinion and Financial Distress has a negative and significant effect on the Going Concern Audit Opinion. Meanwhile, simultaneously the Sustainability Reporting Disclosure Index and Financial Distress have a positive and significant effect on the Going Concern Audit Opinion